Places of Tradition, Places of Research: The Evaluation of Traditional Medicine Workshops Using Culturally and Locally Relevant Methods - Barwin, Lynn (Université d'Ottawa / University of Ottawa, 2012)
This thesis examines how traditional medicine workshops offered by an Aboriginal health centre contribute to capacity re-building through self-care in two local communities in Manitoulin Island, Ontario. Health disparities that exist between Aboriginal people and the rest of the population have prompted a need to better understand health determinants that are of relevance in these communities including the importance of culture, tradition, and self-determination. A variety of qualitative methods were employed in this work including in-depth interviews, focus groups and “art voice.” The use of art voice on Manitoulin Island advances decolonizing methodologies by emphasizing how the incorporation of locally and culturally relevant methods or “methods-in-place,” is an effective way to engage communities in the research process. Results show the need to approach traditional teachings, health programs, and research from an Aboriginal worldview and indicate that more frequent workshops are required to empower youth and adults to practice and share traditional knowledge. Furthermore, a continuum exists in which the interest in language, culture, and tradition increases with age. Capacity can therefore be re-built over time within communities promoting autonomy and self-determination through self-care. Findings can be expected to further inform the traditional programming in participating communities, enhance existing Aboriginal determinants of health models by including traditional medicine as an element of self-care, and can act as a springboard for the inclusion of unique place-based methods into community-based research projects in the future.
Keywords: Aboriginal health; traditional medicine; self-care; capacity (re)building; decolonizing methodology; self-determination; art voice; culturally relevant research; place-based methods; decolonizing methods; Manitoulin School of Art; Indigenous Worldview